Analysis of the Citizen’s Attitudes About the Economic Measures to Eliminate the Consequences of the COVID-19 Pandemic in the Republic of Serbia - Dimitrijević, Dragomir; Kostić, Milan; Radulović, Marija (Naše gospodarstvo/Our economy, 2025)
The pandemic caused by the COVID-19 virus has led to negative economic consequences in all countries. The COVID-19 pandemic created problems in the functioning of the economy, and economic state measures were necessary to reduce the negative impact of the pandemic. Every country in the world has tried to find the best economic measures to help its citizens overcome the negative effects of the pandemic as easily as possible. After 5 years since the pandemic began, the real effects of these state measures, which were also implemented by the Government of the Republic of Serbia, can now be seen much more objectively, which is analysed in this paper. The primary objective of this paper is to evaluate citizens' opinions on the effectiveness of the state economic measures implemented by the Government of the Republic of Serbia to mitigate the impact of pandemics on both citizens' lives and companies' operations.